2017
DOI: 10.1002/jclp.22522
|View full text |Cite
|
Sign up to set email alerts
|

Emotion‐related impulsivity and rumination predict the perimenstrual severity and trajectory of symptoms in women with a menstrually related mood disorder

Abstract: Both rumination and emotion-related impulsivity may be important treatment targets in cognitive behavioral interventions aimed at reducing symptom severity and cyclicity in MRMDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 40 publications
1
16
0
Order By: Relevance
“…Subsequent research has confirmed heightened levels of impulsivity with both PMDD and premenstrual symptom severity (e.g. Dawson et al 2018;Petersen et al 2016), making this a hypothesis that would benefit from future research. Future research should also be directed at the clinically most meaningful assessment of impulsivity in this group of women and its role as a potential risk factor alongside the role that personality traits may play.…”
Section: Discussionmentioning
confidence: 87%
“…Subsequent research has confirmed heightened levels of impulsivity with both PMDD and premenstrual symptom severity (e.g. Dawson et al 2018;Petersen et al 2016), making this a hypothesis that would benefit from future research. Future research should also be directed at the clinically most meaningful assessment of impulsivity in this group of women and its role as a potential risk factor alongside the role that personality traits may play.…”
Section: Discussionmentioning
confidence: 87%
“…psychological factors associated with prospectively-diagnosed PMDD and severity of symptom expression. Compared with controls, patients with PMDD show higher trait levels of brooding rumination (Craner, Sigmon, Martinson, & McGillicuddy, 2014), and higher brooding rumination among patients with PMDD prolonged residual symptoms in the early follicular phase (Dawson et al, 2018). Patients with PMDD also report higher trait levels of avoidant or impulsive behaviors than controls (Craner et al, 2014;Petersen et al, 2016).…”
Section: Psychosocial Mechanisms In Pmdd a Small Number Of Studies Hmentioning
confidence: 92%
“…The C-PASS scoring system (Eisenlohr-Moul et al, 2017), including the excel and SAS macro, can be used in research either to diagnose individuals categorically (e.g., individual A meets criteria for PMDD across two cycles of daily ratings, whereas individual B does not) and measure symptom cyclicity dimensionally (e.g., individual A showed an average of 45% premenstrual elevation of depression across two cycles; individual B showed an average of 28% premenstrual elevation of depression across two cycles). In addition to these methods, which use daily ratings to create between-person variables, daily symptoms can also be modeled directly as repeated outcomes in multilevel models, using coded menstrual cycle variables (Schmalenberger & Eisenlohr-Moul, 2019) as categorical or continuous predictors (e.g., as in (Dawson et al, 2018;.…”
Section: How To Study Pmdsmentioning
confidence: 99%
“…Although PMDD generally demonstrates symptom offset during or just after menses, several studies have noted variability in the timing and speed of this symptom offset. There appears to be a normative rapid symptom offset in the first 3 days of menses (Pearlstein et al ., 2005), but some symptoms, especially those related to depression, sometimes demonstrate a slower offset in PMDD (Bancroft et al ., 1994; Dawson et al ., 2018) and in PME of borderline personality disorder (Eisenlohr-Moul et al ., 2018 b ). Although the mechanisms of these offset differences remain relatively understudied, both emotion regulation strategies (Dawson et al ., 2018) and differences in response to hormone withdrawal (Eisenlohr-Moul et al ., 2018 a , 2018 b ) may play a role.…”
Section: Introductionmentioning
confidence: 99%
“…(2017)]. Consistent with previous work (e.g. Bancroft et al ., 1994; Dawson et al ., 2018; Eisenlohr-Moul et al ., 2018 a , 2018 b ), we also hypothesized that, especially for depressive symptoms, one trajectory group would show a late offset of symptoms, with symptoms arising at any point in the luteal phase but remitting more slowly or incompletely in the menstrual and postmenstrual weeks.…”
Section: Introductionmentioning
confidence: 99%